Crosstalk Interferences on Impedance Measurements in Battery Packs*. Issue 11 (2016) - Raijmakers, L.H.J.; Shivakumar, K.M.; Donkers, M.C.F.; Lammers, M.J.G.; Bergveld, H.J.
Abstract: In order to provide the required power and energy for e.g. automotive applications, a multitude of cells is assembled into a battery pack. For safety and control purposes it is of interest to equip every single cell with an Electrochemical Impedance Spectroscopy (EIS) measurement system. However, performing EIS measurements simultaneously on each cell in a battery pack introduces crosstalk interferences in surrounding cells. This causes EIS measurements in battery packs to be inaccurate. An experimental investigation on a battery pack showed that crosstalk is a linear phenomenon which is dependent on the measurement frequency, the relative position of the cells and the inter-cell spacing. Based on the experimental results and a proposed two-coil model with inductive coupling, a transfer-function description has been developed in order to simulate the crosstalk behavior. This model can be used as a supporting tool in the development of ElS-based measurement systems in battery packs.